Pengaruh Penggunaan Teknologi Pada Proses Pembelajaran Pendidikan Agama Islam di Sekolah - Fauzi, Muhammad Nur; Shiddiq, Muhammad Ja’far; Kirana, Maharani Galuh; Putra, Purnama (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2024)
The purpose of this research is to analyze the impact of technology usage on the learning process of Islamic Religious Education (PAI). In today's digital era, the integration of technology in education has become increasingly important to enhance the effectiveness and efficiency of the learning process. The research method employed is simple regression analysis, with data collected from 50 respondents involved in PAI learning across various educational institutions. The analysis results indicate that technology usage has a positive and significant effect on the PAI learning process, with a coefficient value of 0.765 and a significance value (p-value) of 0.000. The obtained t-value is 8.316, demonstrating that the impact of technology usage on PAI learning is very strong. These findings emphasize the importance of implementing technology in education to improve the quality of learning and student outcomes. This study recommends that educators and education managers strengthen the integration of technology into the PAI curriculum to achieve better educational goals. This abstract encompasses the background, research objectives, methods, results, and recommendations, providing a comprehensive overview of the research content